Trends in bilateral oophorectomy at the time of hysterectomy for benign disease - Novetsky, Akiva P; Boyd, Leslie R; Curtin, John P (Obstetrics and gynecology (New York. 1953), 2011)
To identify patient characteristics associated with bilateral oophorectomy or removal of remaining ovary at the time of benign hysterectomy, and to estimate trends in the performance of oophorectomy from 2001 to 2006. This was a cross-sectional analysis using the New York State Department of Health Statewide Planning and Research Cooperative System. Women aged 18 years or older undergoing hysterectomies for benign gynecologic conditions were included. We evaluated factors associated with oophorectomy on both univariable and multivariable analyses and assessed for changes in performance of oophorectomy over the course of the study. Forty-seven percent of 144,877 hysterectomies included oophorectomy. Women who underwent oophorectomy were older and were more likely to have a family history of breast or ovarian cancer, a personal history of breast cancer, ovarian cysts, or endometriosis. Women who underwent vaginal or laparoscopic hysterectomy or had uterine prolapse were less likely to undergo oophorectomy. Both race and insurance status were associated with performance of oophorectomy. From 2001 to 2006, there was an 8% absolute decrease in the performance of oophorectomy at the time of benign hysterectomy for women of all ages, with a 10.4% decrease in women aged younger than 55 (P for trend <.001). Age, route of hysterectomy, and concomitant gynecologic diagnoses influence oophorectomy rate. From 2001 to 2006, a significant decrease in the performance of oophorectomy at the time of benign hysterectomy was noted in women aged younger than 55 years. Recent studies of complications of hormone therapy and prophylactic oophorectomy may have influenced patients' and physicians' decision-making, leading to lower oophorectomy rates. II.